Socialization of KKNT Kadiri Islamic University in Tanggung Village, Tulungagung Darat Sub-District - Nunuk Helilusiatiningsih; Sumarji (Asian Journal of Community Services, 2023)
Responsibility Village is one of the villages located in Tulungagung Regency. It is a lowland area and has an area of 554,184 ha. KKNT aims to give students broad experience and insight and develop knowledge in society. The method of implementation is site surveys, interviews, MSME coaching, counseling in the fields of animal husbandry, agriculture, culture, and increasing cooperation in the KKNT program. The results resulted in 7 types of work programs covering the field of online marketing, MSMEs, WEB Training, and the Catapult Competition Cultural Week by giving prizes, block materials, planting horticultural seeds in 33 polybags planted with oranges and avocados at the Mount Budeg tourist location, compensation for orphans. So the results are useful for increasing the village's potential.